2002
DOI: 10.4049/jimmunol.169.2.898
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Spontaneous Apoptosis of Neutrophil Granulocytes by the Intracellular Parasite Leishmania major

Abstract: Macrophages are the major target cell population of the obligate intracellular parasites Leishmania. Although polymorphonuclear neutrophil granulocytes (PMN) are able to internalize Leishmania promastigotes, these cells have not been considered to date as host cells for the parasites, primarily due to their short life span. In vitro coincubation experiments were conducted to investigate whether Leishmania can modify the spontaneous apoptosis of human PMN. Coincubation of PMN with Leishmania major promastigotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
244
1
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(265 citation statements)
references
References 47 publications
7
244
1
13
Order By: Relevance
“…The higher NET induction by promastigotes relative to LPG could be explained by other NET-inducing molecules and/or the complex membrane structure of the promastigotes, including the fact that LPG shares domains with other Leishmania membrane molecules, such as acid phosphatase, proteophosphoglycan, and glycosylinositolphospholipids (10), which might contribute to NET formation. Previous reports showed that human neutrophils are able to ingest and kill Leishmania (19), but recent studies described that not all ingested promastigotes are destroyed within these cells (13,20,21). Here, we report that a phagocytosis-independent killing mechanism, mediated by neutrophil NETs, is effective against Leishmania promastigotes, and, as reported for bacteria and fungi (2,3,5), Leishmania are killed by NETs.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The higher NET induction by promastigotes relative to LPG could be explained by other NET-inducing molecules and/or the complex membrane structure of the promastigotes, including the fact that LPG shares domains with other Leishmania membrane molecules, such as acid phosphatase, proteophosphoglycan, and glycosylinositolphospholipids (10), which might contribute to NET formation. Previous reports showed that human neutrophils are able to ingest and kill Leishmania (19), but recent studies described that not all ingested promastigotes are destroyed within these cells (13,20,21). Here, we report that a phagocytosis-independent killing mechanism, mediated by neutrophil NETs, is effective against Leishmania promastigotes, and, as reported for bacteria and fungi (2,3,5), Leishmania are killed by NETs.…”
Section: Discussionsupporting
confidence: 49%
“…Neutrophils are rapidly recruited to the bite site, are activated, and ingest and kill parasites (11,12). However, some phagocytosed parasites resist the killing mechanisms triggered in the phagolysosomes, delaying neutrophil apoptosis long enough to allow macrophage arrival at the infection site (11,13). Interestingly, it has been shown that apoptotic neutrophils harboring intracellular parasites are then phagocytosed by macrophages (13).…”
mentioning
confidence: 99%
“…Immediately after infection, granulocytes are attracted by a local inflammatory process (53) and phagocytose the parasites (54). The intracellular parasites survive in the granulocytes and increase the lifespan of their hosts.…”
Section: Employment Of Apoptotic Trojan Horses By Microorganisms To Tmentioning
confidence: 99%
“…In a second wave of leukocyte invasion 1-2 days after infection, macrophages are recruited and remove apoptotic granulocytes harboring viable parasites. Since the uptake of apoptotic cells does not activate the antimicrobial effector mechanisms (55), the parasites can now survive in the macrophages (54).…”
Section: Employment Of Apoptotic Trojan Horses By Microorganisms To Tmentioning
confidence: 99%
“…Indeed, there appears to be distinct differences in the way various species of Leishmania result in activation and otherwise affect neutrophils [10,2123]. In the context of disease progression, it has been suggested that, rather than control the infection, neutrophils exacerbate disease onset either by delaying apoptosis, by impairing activation of dendritic cells, or by serving as a vehicle route for silent entry of the parasite [4,2426]. …”
Section: Introductionmentioning
confidence: 99%